2017
DOI: 10.1101/168898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trade-off and flexibility in the dynamic regulation of the cullin-RING ubiquitin ligase repertoire

Abstract: Cullin-RING ubiquitin ligases (CRLs) catalyze the ubiquitylation of substrates many of which are degraded by the 26S proteasome. Their modular architecture enables recognition of numerous substrates via exchangeable substrate receptors that competitively bind to a cullin scaffold with high affinity. Due to the plasticity of these interactions there is ongoing uncertainty how cells maintain a flexible CRL repertoire in view of changing substrate loads. Based on a series of in vivo and in vitro studies, differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…By deneddylating cullins, the CSN is a key regulator of CRLs (Deshaies and Joazeiro, 2009;Dubiel et al, 2018;Wolf et al, 2003). CSN-mediated deneddylation protects CRLs from autoubiquitylation (Schmidt et al, 2009;Wee et al, 2005;Zhou et al, 2003) and allows the CRL network to adapt to fluctuations in substrate availability (Dubiel et al, 2013(Dubiel et al, , 2015aLiu et al, 2018;Pierce et al, 2013;Reitsma et al, 2017;Straube et al, 2017;Wu et al, 2013;Zemla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By deneddylating cullins, the CSN is a key regulator of CRLs (Deshaies and Joazeiro, 2009;Dubiel et al, 2018;Wolf et al, 2003). CSN-mediated deneddylation protects CRLs from autoubiquitylation (Schmidt et al, 2009;Wee et al, 2005;Zhou et al, 2003) and allows the CRL network to adapt to fluctuations in substrate availability (Dubiel et al, 2013(Dubiel et al, , 2015aLiu et al, 2018;Pierce et al, 2013;Reitsma et al, 2017;Straube et al, 2017;Wu et al, 2013;Zemla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best studied E3 ligase complexes are members of the CRL family which engage interchangeable substrate receptor/adapter complexes for substrate-specific ubiquitylation. Substrate receptor assembly is kept in a highly dynamic state (Reitsma et al, 2017;Straube et al, 2017), whereby specific expression of substrate receptors in response to external and internal cellular cues, as well as in a cell-type and tissue specific way, allows the formation of CRLs for selective and efficient client substrate ubiquitylation (Gupta et al, 2013;McGourty et al, 2016;Ravenscroft et al, 2013). Recently, the activity of the multiprotein yeast GID (orthologue of human CTLH complex) was shown to be predominantly regulated by engaging interchangeable substrate receptors, which conceivably target distinct substrates for degradation (Chrustowicz et al, 2021;Kong et al, 2021;Liu & Pfirrmann, 2019;Melnykov et al, 2019;Shin et al, 2021)(Langlois et al 2021 BioRxiv doi: https://doi.org/10.1101/2021.09.02.458684).…”
Section: Discussionmentioning
confidence: 99%
“…We next expanded our analysis to the K562 cells (Figure 6C). Parental and knock-out K562 cell lines were ether treated with NaB to induce erythroid-like or with 12-O-Tetradodecanoyl-phorbol-13 acetate (TPA, chemical activator of PKC kinase) to induce megakaryocyte-like differentiation (Tabilio et al, 1983). Both, NaB and TPA efficiently induced UBE2H protein levels in parental cells suggesting that UBE2H regulation is not restricted to erythroid differentiation (Figure 6D and 6E).…”
Section: Cellular Abundance Of Ube2h Is Coupled To Functional Maeamentioning
confidence: 99%
“…5). Mathematical models have shown that there exist intrinsic trade-offs in molecular exchange systems (Goryachev and Pokhilko, 2006;Straube et al, 2017) which, in the case of the GTPase cycle, predict an optimal concentration for the GEF as a result of a trade-off between high GTPase activity and fast GDP/GTP cycling.…”
Section: Cooperativity and Molecular Exchange Systemsmentioning
confidence: 99%